The Effect of Motivation, Workload and Compensation on the Performance of Non-Civil Servant Employees of Ganesha Education University - MASTIASIH, Made; SUARMANAYASA, I Nengah; RAHMAWATI, Putu Indah (Journal of Tourism Economics and Policy, 2025)
This study aims to analyze the influence of motivation, workload, and compensation on the performance of non-civil servant (PNS) employees at Ganesha University of Education. Non-PNS employees have an important role in supporting university operations, therefore it is important to understand the factors that influence their performance. This study uses a quantitative approach with a survey method. Data were obtained by distributing questionnaires to non-PNS employees at Ganesha University of Education. The sample of this study consisted of 189 non-PNS employee respondents who had various positions and responsibilities in various work units at the university. The results of the data analysis showed that motivation, workload, and compensation had a significant effect on the performance of non-PNS employees at Ganesha University of Education. Motivation of non-PNS employees has a positive effect on employee performance, where employees who have high motivation tend to show better performance. Meanwhile, workload has a negative effect on the performance of non-PNS Undiksha employees. The higher the workload given, the employee performance tends to decrease. Fair and adequate compensation also has a positive impact on the performance of non-PNS employees. Motivation, workload, and compensation have a significant effect on the performance of non-PNS employees at Ganesha University of Education. The results of this study imply that Ganesha University of Education should enhance non-PNS employee performance by improving motivation through recognition, rewards, and career development. Additionally, establishing workload and compensation standards is essential to ensure fairness based on employee contributions.